Civil Society in Vietnam: A Comparative Study of Civil Society Organizations in Hanoi and Ho Chi Minh City - William Taylor; Nguyễn Thu Hằng; Phạm Quang Tú; Huỳnh Thị Ngọc Tuyết; William Taylor; Nguyễn Thu Hằng; Phạm Quang Tú; Huỳnh Thị Ngọc Tuyết
This comparative research project provides an overview of civil society organizations (CSOs) in Vietnam. The research was carried out in Vietnam’s two major metropolitan areas, Hanoi and Ho Chi Minh City, which are the bases for the majority of Vietnamese CSOs. The research team selected fifty representative CSOs from each city, interviewing leaders of those organizations on multiple aspects of civil society operation and development. The findings focus on civil society governance, programmatic focus, operational approaches, forms of engagement with other sectors such as businesses and government, networking, and funding.